Room-temperature curing phosphate anticorrosive coating as well as preparation method and application thereof
The silane coupling agent modified magnesium oxide and aluminum dihydrogen phosphate binder base combined with aluminum hydroxide and silica filler were prepared to prepare room-temperature cured phosphate anticorrosion coatings, solving the problems of high curing temperature and complex operation of existing anticorrosion coatings, achieving efficient room-temperature curing and excellent anticorrosion effect.
Patent Information
- Application Number
- CN202510210686.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
AI Technical Summary
The existing anticorrosion coatings have high curing temperature and complex operation during construction, and some fillers are expensive and difficult to obtain, making them difficult to achieve room temperature curing and practical application.
Magnesium oxide is modified by silane coupling agent, and the reaction of phosphoric acid with aluminum hydroxide is made to form an aluminum dihydrogen phosphate binder base material. Combined with aluminum hydroxide and silica filler, a room-temperature cured phosphate anticorrosion coating is prepared.
The coating is fully cured at room temperature, significantly extending the operability time, improving the adhesion, hardness and wear resistance of the coating, and significantly improving the corrosion resistance of Q235 carbon steel.
Smart Images

Figure CN119899549A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional coatings, and more particularly to a room temperature curing phosphate anticorrosive coating and a preparation method and application thereof. Background Art
[0002] Anti-corrosion coatings are a kind of protective layer used on metal surfaces to isolate metal from the surrounding medium, thereby controlling corrosion and extending the service life of the metal. Traditional anti-corrosion coatings are mostly organic solvent-based and contain a large amount of volatile organic compounds. If used rashly, they will cause irreversible damage to steel and pollute the environment during construction. Therefore, the development of inorganic anti-corrosion coatings has become a trend in the development of the coatings industry.
[0003] In recent years, there have been considerable reports on the research of inorganic anticorrosive coatings. Representative reports mainly include:
[0004] (1) In 2017, Ma Chengkun's research group at Harbin Engineering University found that using aluminum dihydrogen phosphate as a binder, alumina as a filler and curing agent and adding 15 wt% of nano-aluminum nitride and other nanomaterials can significantly reduce the curing temperature of the adhesive to 70°C and improve its shear strength. However, nano-aluminum nitride is relatively expensive and the final curing temperature is 70°C, which is not conducive to practical application (Ma, C.; Chen, H.; Wang, C.; Zhang, J.; Qi, H.; Zhou, L. Effects of Nano-Aluminum Nitride on the Performance of an Ultrahigh-Temperature Inorganic Phosphate Adhesive Cured at Room Temperature. Materials 2017, 10, 1266.).
[0005] (2) In 2019, Yang Mei's research group at Chengdu University of Technology studied a low-temperature curing aluminum phosphate coating developed on Ti-6Al-4V alloy. By using T-ZnOw@Al2O3 core-shell curing agent and aluminum powder filler, low-temperature curing of 120 minutes at 70°C was achieved, significantly reducing the curing temperature and time of the coating and improving the coating hardness. In addition, the addition of aluminum powder improved the surface roughness of the coating and the oxidation resistance at 800°C. Finally, a smooth aluminum phosphate coating was obtained when the mass ratio of P:Zn:Al was 10:1:0.05 (Liu, F.; Yang, M.; Han, B.; Long, J. Development of T-ZnOw@Al2O3-incorporated low-temperature curing aluminium phosphate coating on Ti-6Al-4V alloy. Ceram. Int. 2019, 45, 18406-18412.).
[0006] (3) In 2020, Dong Yinsheng's research group at Southeast University studied an aluminum phosphate anti-corrosion coating prepared on the surface of cast aluminum-silicon alloy by dip coating and steam-assisted curing. The coating is mainly composed of AlPO4 and AlPO4·1.5H2O, and exhibits excellent interfacial adhesion and significantly improved corrosion resistance (Huang, X.; Wang, D.; Dong, Y. Corrosion resistance phosphate coating formed by steam assisted curing on castAl-Sialloy. Surface & Coatings Technology 2020, 382, 125242.).
[0007] Summarizing the existing anti-corrosion coating methods, it is not difficult to see that most anti-corrosion coatings only achieve low-temperature curing and have poor practical applicability, so there are the following problems:
[0008] (1) In the actual construction process, the curing of the coating requires a lower temperature and a simpler operation method to facilitate construction and use;
[0009] (2) Some fillers in coatings are expensive and difficult to obtain.
[0010] Therefore, how to develop an inorganic anti-corrosion coating that can be cured at room temperature is an urgent problem that technicians in this field need to solve. Summary of the invention
[0011] In view of this, the purpose of the present invention is to provide a room temperature curing phosphate anti-corrosion coating and a preparation method and application thereof, so as to solve the deficiencies in the prior art.
[0012] In order to achieve the above object, the present invention adopts the following technical solution:
[0013] A method for preparing a room temperature curing phosphate anticorrosive coating, specifically comprising the following steps:
[0014] (1) mixing a silane coupling agent with an ethanol aqueous solution, dispersing the mixture, and obtaining a modified liquid;
[0015] (2) mixing the modified liquid with magnesium oxide, heating and stirring, filtering, washing, drying, and grinding to obtain modified magnesium oxide for later use;
[0016] (3) mixing aluminum hydroxide and water, heating and stirring, adding phosphoric acid, and continuing to stir after heating to obtain aluminum dihydrogen phosphate;
[0017] (4) Mix aluminum dihydrogen phosphate and water, stir, add aluminum hydroxide and silicon dioxide, continue stirring, add the aqueous dispersion of modified magnesium oxide, mix and stir, and obtain a room temperature curing phosphate anti-corrosion coating.
[0018] Furthermore, in the above step (1), the silane coupling agent is at least one of KH151, KH171, KH550, KH560, KH570 and KH792, preferably KH560 and KH570; the amount of the silane coupling agent is 0.01%-12% of the mass of magnesium oxide, preferably 6% or 8%.
[0019] The above further beneficial effect is that the present invention innovatively uses a silane coupling agent to modify the curing agent magnesium oxide, so that a dense silane film is uniformly formed on the surface of magnesium oxide, and the film can effectively delay the MgO 2+ In addition, the addition of silane coupling agent significantly improves the bonding strength and water resistance of the coating, while making it easier to evenly disperse magnesium oxide in the coating system, effectively reducing agglomeration, and making the structure of the cured coating more uniform and dense.
[0020] Furthermore, in the above step (1), the volume ratio of ethanol to water in the ethanol aqueous solution is 4:1; the dispersion method is a shaking table, magnetic stirring or ultrasonic dispersion, the temperature is 35°C, and the time is 1-2h.
[0021] Furthermore, in the above step (2), the mass ratio of the modified liquid to magnesium oxide is 4:1; the heating and stirring equipment is an oil bath pot, the temperature is 50-100°C, preferably 60-80°C, the time is 1-2h, preferably 2h; the washing reagent is anhydrous ethanol, the number of times is 2-4 times; the drying equipment is an oven, the temperature is 120°C.
[0022] A further beneficial effect of the above method is that appropriately increasing the amount of modified magnesium oxide can not only enable the coating to cure at room temperature, but also significantly extend the operating time of the coating, thereby avoiding the coating being unable to be used normally due to too fast a curing speed.
[0023] Furthermore, in the above step (3), the heating and stirring device is an oil bath pot, and the temperature is 80-90°C; the stirring temperature is continued at 98-120°C, and the time is more than 2 hours, until the solution is completely transparent.
[0024] Furthermore, in the above step (4), the mass ratio of aluminum dihydrogen phosphate, aluminum hydroxide, silicon dioxide and modified magnesium oxide is 46: (0.01-20): (0.01-12): (0.01-10), preferably 46:16:11:1 or 46:16:11:2; the stirring speed is 500-800r / min; the stirring time is continued for 5-10min; and the mixing time is 15-20min.
[0025] A further beneficial effect of adopting the above is that aluminum hydroxide and silicon dioxide as fillers can fill the gaps and holes in the coating, thereby further enhancing the anti-corrosion effect and hardness of the coating.
[0026] The present invention also claims protection for a room temperature curing phosphate anti-corrosion coating prepared by the above preparation method.
[0027] The present invention also seeks to protect the use of a room temperature curing phosphate anti-corrosion coating prepared by the above preparation method in the preparation of an anti-corrosion coating.
[0028] Furthermore, the preparation method of the above-mentioned anti-corrosion coating is: apply the room temperature curing phosphate anti-corrosion coating obtained by the above-mentioned preparation method to the treated Q235 carbon steel plate, place it in a ventilated place, and bake it to obtain the anti-corrosion coating.
[0029] Furthermore, the coating method is spraying, roller coating or brushing, preferably brushing; the placement time is 1 hour; the baking equipment is an oven, the temperature is 35° C., and the time is 2-6 hours, until it is completely cured.
[0030] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0031] 1. The present invention first uses a silane coupling agent to modify the curing agent magnesium oxide, then uses phosphoric acid and aluminum hydroxide to react to generate a dihydrogen phosphate aluminum binder base material, and finally compound the modified magnesium oxide, the dihydrogen phosphate aluminum binder base material, aluminum hydroxide and silicon dioxide filler. The coating thus prepared can be completely cured at room temperature, and forms good adhesion strength with the treated Q235 carbon steel substrate, and is not easy to fall off during use.
[0032] 2. The coating of the present invention exhibits excellent performance in a neutral salt spray resistance test and can last for more than 720 hours, significantly improving the corrosion resistance of Q235 carbon steel.
[0033] 3. The coating of the present invention has the excellent property of curing at room temperature due to its optimized formula and structure, and has strong adhesion, high density, high strength and good wear resistance. It can effectively protect the metal substrate from corrosion and is suitable for anti-corrosion applications in large ships and other fields, and has broad practical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 SEM images of the anti-corrosion coatings prepared from the anti-corrosion coatings of Q235 carbon steel plate, Comparative Example 1, Comparative Example 2 and Example 1;
[0035] Figure 2 The weight loss curves of the anti-corrosion coatings prepared from the anti-corrosion coatings of Comparative Example 3, Comparative Example 1 and Example 1 at a constant temperature of 35°C. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation method of room temperature curing phosphate anticorrosive coating (modified curing agent) specifically comprises the following steps:
[0039] (1) 0.372 g of silane coupling agent KH570 was mixed with 29.16 g of ethanol and 7.28 mL of water, and then ultrasonically dispersed at 35 °C for 1 h to obtain a modified liquid;
[0040] (2) First, 18.6 g of the modified liquid was mixed with 4.65 g of magnesium oxide, and then placed in an oil bath, heated to 70° C. and stirred for 2 h, filtered, and repeatedly washed with anhydrous ethanol for 3 times, and finally placed in an oven at 120° C. to dry and grind to obtain modified magnesium oxide for later use;
[0041] (3) First, 18.32 g of aluminum hydroxide was mixed with 28.8 mL of water, and then placed in an oil bath and heated to 90° C. and stirred. Then, 69.19 g of 85 wt % phosphoric acid was added, and the temperature was raised to 98° C. and stirred for 2 h until the solution was completely transparent, thereby obtaining aluminum dihydrogen phosphate;
[0042] (4) First, 37 g of aluminum dihydrogen phosphate was mixed with 10 mL of water, and stirred at a speed of 500 r / min. Then, 13 g of aluminum hydroxide and 9 g of silicon dioxide were added, and stirring was continued for 5 min. Finally, 2 g of modified magnesium oxide dispersed in 8 mL of water was added, and the mixture was mixed and stirred for 15 min to obtain a room temperature curing phosphate anti-corrosion coating.
[0043] Comparative Example 1
[0044] The preparation method of phosphate anticorrosive coating (unmodified curing agent) specifically comprises the following steps:
[0045] (1) First, 18.32 g of aluminum hydroxide was mixed with 28.8 mL of water, and then placed in an oil bath and heated to 90° C. and stirred. Then, 69.19 g of 85 wt % phosphoric acid was added, and the temperature was raised to 98° C. and stirred for 2 h until the solution was completely transparent, thereby obtaining aluminum dihydrogen phosphate;
[0046] (2) First, 37 g of aluminum dihydrogen phosphate was mixed with 10 mL of water, and stirred at a speed of 500 r / min. Then, 13 g of aluminum hydroxide and 9 g of silicon dioxide were added, and stirring was continued for 5 min. Finally, 2 g of magnesium oxide dispersed in 8 mL of water was added, and the mixture was mixed and stirred for 15 min to obtain a phosphate anti-corrosion coating.
[0047] Comparative Example 2
[0048] The preparation method of phosphate anticorrosive coating (without filler) specifically comprises the following steps:
[0049] (1) 0.372 g of silane coupling agent KH570 was mixed with 29.16 g of ethanol and 7.28 mL of water, and then ultrasonically dispersed at 35 °C for 1 h to obtain a modified liquid;
[0050] (2) First, 18.6 g of the modified liquid was mixed with 4.65 g of magnesium oxide, and then placed in an oil bath, heated to 70° C. and stirred for 2 h, filtered, and repeatedly washed with anhydrous ethanol for 3 times, and finally placed in an oven at 120° C. to dry and grind to obtain modified magnesium oxide for later use;
[0051] (3) First, 18.32 g of aluminum hydroxide was mixed with 28.8 mL of water, and then placed in an oil bath and heated to 90° C. and stirred. Then, 69.19 g of 85 wt % phosphoric acid was added, and the temperature was raised to 98° C. and stirred for 2 h until the solution was completely transparent, thereby obtaining aluminum dihydrogen phosphate;
[0052] (4) First, 37 g of aluminum dihydrogen phosphate was mixed with 10 mL of water, and stirred at a speed of 500 r / min. Then, 2 g of modified magnesium oxide dispersed in 8 mL of water was added, and the mixture was stirred for 15 min to obtain a phosphate anti-corrosion coating.
[0053] Comparative Example 3
[0054] The preparation method of phosphate anticorrosive coating (without curing agent) specifically comprises the following steps:
[0055] (1) First, 18.32 g of aluminum hydroxide was mixed with 28.8 mL of water, and then placed in an oil bath and heated to 90° C. and stirred. Then, 69.19 g of 85 wt % phosphoric acid was added, and the temperature was raised to 98° C. and stirred for 2 h until the solution was completely transparent, thereby obtaining aluminum dihydrogen phosphate;
[0056] (2) First, 37 g of aluminum dihydrogen phosphate was mixed with 10 mL of water, and stirred at a speed of 500 r / min. Then, 13 g of aluminum hydroxide and 9 g of silicon dioxide were added, and stirring was continued for 5 min to obtain a phosphate anti-corrosion coating.
[0057] Comparative Example 4
[0058] Low-temperature curing anti-corrosion coatings reported in the literature (Xu, S.-Q.; Ding, C.-H.; Wang, G.-Q.; Jiang, H.; Li, J.; Wang, P.-Q. Preparation and Research of an Inorganic Phosphate Anticorrosive Coating with MgO@SiO2 Curing Agent. Corrosion&Protection 2015, 36(10), 972-977.).
[0059] The preparation method specifically comprises the following steps:
[0060] (1) Prepare a mixture of ethanol, deionized water and ammonia water, and slowly add a mixed solution of ethyl orthosilicate and ethanol under rapid stirring. After the addition is completed, continue stirring for 0.5 hours to obtain a nano-silica sol. Add a certain amount of MgO powder to the nano-silica sol, ultrasonically disperse it, age it, filter it, wash it and dry it, and finally obtain MgO@SiO2.
[0061] (2) Aluminum phosphate adhesive, titanium dioxide, cross-linking accelerator, etc. are mixed as component A, and MgO@SiO2, barium sulfate, inhibitor, etc. are mixed as component B.
[0062] (3) Components A and B are mixed in a ratio of 20:1. After stirring evenly, the coating begins to react slowly within 30 minutes and is applicable within 120 minutes. The applied coating is baked and cured at 80°C to obtain an anti-corrosion coating with a smooth surface and dense interior.
[0063] Performance Testing
[0064] The anti-corrosion coatings prepared in Example 1 and Comparative Examples 1-4 were respectively applied to the treated Q235 carbon steel plates, and then placed in a ventilated place for 1 hour and cured according to the method in Table 1 to obtain anti-corrosion coatings.
[0065] 1. SEM Characterization
[0066] The SEM images of the anti-corrosion coatings prepared from the treated Q235 carbon steel plate, comparative example 1 (unmodified curing agent), comparative example 2 (no filler) and embodiment 1 (modified curing agent) are as follows: Figure 1 As shown in (a), (b), (c) and (d).
[0067] As can be seen from Table 1, when unmodified magnesium oxide is used in Comparative Example 1, a large number of cracks appear on the coating surface due to the too fast curing speed; a large number of obvious pores and holes exist on the coating surface of Comparative Example 2 without adding fillers; and the coating surface of Example 1 using modified magnesium oxide and adding fillers is smooth and has no cracks.
[0068] 2. Weight loss rate curve
[0069] The weight loss rate curves of the anti-corrosion coatings prepared from the anti-corrosion coatings of Comparative Example 3 (without curing agent), Comparative Example 1 (unmodified curing agent) and Example 1 (modified curing agent) at a constant temperature of 35°C are as follows: Figure 2 shown.
[0070] Depend on Figure 2 It can be seen that the curing process follows the parabolic law. In the case of comparative example 3 without a curing agent, almost no curing reaction occurs at room temperature. In comparative example 1, unmodified ordinary magnesium oxide is added, and the weight loss increases rapidly within 50 minutes, then tends to be stable, and cures rapidly, which is inconvenient for practical application. When the modified curing agent is added to Example 1, the weight loss rate increases rapidly in the early stage of curing, and then slows down, until the curve remains unchanged after 275 minutes, indicating that the curing process is completed.
[0071] 3. Coating performance test
[0072] In order to comprehensively evaluate the performance of the anticorrosive coatings prepared from the anticorrosive coatings of Example 1 (modified curing agent), Comparative Example 1 (unmodified curing agent) and Comparative Example 4, a series of professional instruments were used for precise testing. Among them:
[0073] 1. The adhesion test is carried out using the QFH-A type hundred-grid knife adhesion tester of the ARP brand, strictly in accordance with the GB / T9286-1998 standard.
[0074] 2. The hardness is measured using the RW-5101s electric pencil surface hardness tester produced by Ruiwen Instrument Co., Ltd. and operated in accordance with GB / T 6739-2022 standard to obtain accurate data on the coating hardness.
[0075] 3. The contact angle is measured using the HARKE-SPCAX1 contact angle tester produced by the HARKE Instrument Testing Factory. This instrument can accurately measure the contact angle between the coating surface and water, and then evaluate the hydrophobicity of the coating surface.
[0076] 4. The anti-corrosion effect is tested by the ASR-60A precision salt spray resistance tester produced by Asrui Instrument Technology Co., Ltd. This test strictly follows the GB / T 10125-2021 standard to simulate the salt spray corrosion conditions in the actual use environment, so as to accurately evaluate the anti-corrosion ability of the coating.
[0077] The results are shown in Table 1.
[0078] Table 1 Performance test results of the anticorrosive coatings of Example 1, Comparative Example 1 and Comparative Example 4
[0079]
[0080] As can be seen from Table 1, compared with Comparative Example 1 (unmodified curing agent), the curing time of the coating in Example 1 is significantly prolonged, thereby significantly improving the situation in which a large number of cracks appear on the surface of the coating in Comparative Example 1 due to excessively fast curing speed, thereby significantly improving the neutral salt spray resistance effect. In addition, due to the introduction of the silane coupling agent, the adhesion of the coating is further enhanced and the contact angle is improved.
[0081] Compared with Comparative Example 4, the coating of Example 1 can achieve room temperature curing temperature, and the anti-corrosion effect of the coating is better, which makes the construction operation easier.
[0082] In summary, the room temperature curing phosphate anticorrosive coating of the present invention has a relatively low curing temperature (baking at 35°C for 5 hours) and has a considerable anticorrosive effect, and can effectively protect metal steel from corrosion. In addition, the coating has excellent performance indicators such as adhesion and hardness, making it an ideal choice for a variety of anticorrosive application scenarios.
[0083] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a room temperature curing phosphate anticorrosive coating, characterized in that: The specific steps include: (1) mixing a silane coupling agent with an ethanol aqueous solution, dispersing the mixture, and obtaining a modified liquid; (2) mixing the modified liquid with magnesium oxide, heating and stirring, filtering, washing, drying, and grinding to obtain modified magnesium oxide for later use; (3) mixing aluminum hydroxide and water, heating and stirring, adding phosphoric acid, and continuing to stir after heating to obtain aluminum dihydrogen phosphate; (4) Aluminum dihydrogen phosphate is mixed with water, stirred, aluminum hydroxide and silicon dioxide are added, stirring is continued, and an aqueous dispersion of modified magnesium oxide is added, mixed and stirred to obtain the room temperature curing phosphate anti-corrosion coating.
2. The method for preparing a room temperature curing phosphate anticorrosive coating according to claim 1, characterized in that: In step (1), the silane coupling agent is at least one of KH151, KH171, KH550, KH560, KH570 and KH792; the amount of the silane coupling agent is 0.01%-12% of the mass of magnesium oxide.
3. The method for preparing a room temperature curing phosphate anticorrosive coating according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol aqueous solution is 4:1; the dispersion method is a shaking table, magnetic stirring or ultrasonic dispersion, the temperature is 35° C., and the time is 1-2 h.
4. The method for preparing a room temperature curing phosphate anticorrosive coating according to claim 1, characterized in that: In step (2), the mass ratio of the modified liquid to magnesium oxide is 4:1; the heating and stirring device is an oil bath pot, the temperature is 50-100°C, and the time is 1-2h; the washing reagent is anhydrous ethanol, and the number of times is 2-4 times; the drying device is an oven, and the temperature is 120°C.
5. The method for preparing a room temperature curing phosphate anticorrosive coating according to claim 1, characterized in that: In step (3), the heating and stirring device is an oil bath pot with a temperature of 80-90°C; the temperature for continued stirring is 98-120°C for more than 2 hours until the solution is completely transparent.
6. The method for preparing a room temperature curing phosphate anticorrosive coating according to claim 1, characterized in that: In step (4), the mass ratio of aluminum dihydrogen phosphate, aluminum hydroxide, silicon dioxide and modified magnesium oxide is 46: (0.01-20): (0.01-12): (0.01-10); the stirring speed is 500-800r / min; the continued stirring time is 5-10min; and the mixing and stirring time is 15-20min.
7. A room temperature curing phosphate anti-corrosion coating prepared by the preparation method according to any one of claims 1 to 6.
8. Use of a room temperature curing phosphate anti-corrosion coating prepared by the preparation method according to any one of claims 1 to 6 in the preparation of an anti-corrosion coating.
9. The use according to claim 8, characterized in that: The preparation method of the anti-corrosion coating is: applying the room temperature curing phosphate anti-corrosion coating obtained by the preparation method as described in any one of claims 1 to 6 to the treated Q235 carbon steel plate, placing it in a ventilated place, and baking to obtain the anti-corrosion coating.
10. The use according to claim 9, characterized in that: The coating method is spraying, rolling or brushing; the placement time is 1 hour; the baking equipment is an oven, the temperature is 35° C., and the time is 2-6 hours, until it is completely cured.